Comprehensive Evaluation of Harmonic Analysis and Mitigation Approaches for Distribution Networks: A Comparative Study across three Distinct Network Load Scenarios - Tom Wanjekeche; Josephat Simeon; Vilho Nghuumbwa; Andreas. Ndapuka (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
Distribution networks are essential components of modern power systems, catering to diverse consumer needs. However, the escalating demand for electricity has amplified concerns regarding harmonics stemming from non-linear loads. These harmonics pose significant threats to power quality and equipment integrity. This paper conducts a thorough examination of harmonic analysis and mitigation strategies within distribution networks, with a specific focus on three distinct load scenarios: low power factor, residential areas, and university campus. By evaluating harmonic levels, frequency components, and voltage distortions across these scenarios, it provides insights into their unique challenges. Moreover, the research explores mitigation techniques to address identified harmonic issues effectively. The findings not only enhance the understanding of harmonic problems in distribution networks but also offer practical solutions to enhance power quality and network reliability. This paper serves as a valuable resource for power system engineers, utility companies, and researchers involved in distribution network management.